The Main Stages of the Formation of Israel National Innovation System in the XX Century - I. G. Korotkov (Мир новой экономики, 2019)
From the middle of the XIX century up to the end of the XX century, Israel has developed from an agrarian country to the country with an industrial economy and advanced science sector. A significant part of the immigrants of the Jewish community of Palestine were representatives of academic science and engineers. Their number was periodically replenished by highly educated immigrants from Europe. Scientists, university professors and engineers have become the only “natural” resource available to the country in abundance. The first successes Israel scientists have achieved in the field of agriculture — they invented the drip irrigation and its hybrid varieties, leading to high yields in severe local conditions. The Office of the Chief Scientist (OCS), established in 1969, played a leading role in the development of Israeli science and technology. The influence of the military-industrial complex on the formation of Israel NIS was significant. The high technologies developed for the Israel Defense Forces (IDF) were further adapted for the civilian market. IDF has also become a provider of highly qualified personnel for civilian industries. In 1950–1960 Israel established specialized transfer companies based on leading national universities to commercialise technologies developed at universities and research institutes. The successful experience of state support of innovations in Israel has become an example for many countries, including Russia.